PESAN EDUKASI PROMOSI KESEHATAN PADA IKLAN LAYANAN MASYARAKAT DI MEDIA SOSIAL - Rini Riyantini (Jurnal Pustaka Komunikasi, 2023)
The purpose of this study is to analyze the video content of the public service advertisement (PSA) for the covid-19 vaccine of the Ministry of Health of the Republic of Indonesia uploaded on YouTube. A quantitative approach using the content analysis method was used in this study to describe message content based on the concept of educational messages from the development communication theory, communication, information and education model. The research object consists of 3 (three) videos with a 30 seconds each duration and 64 scenes. The analysis was carried out by coding educational messages consisting of verbal and nonverbal messages by 2 coders. The results showed that the PSA video covid 19 vaccine of Indonesian Ministry of Health's contains educational messages with dominant elements of encouraging learning for lyrical and written for verbal messages, while nonverbal educational messages of music and expression are dominated by elements of attitude formation. Construct validity is used to guarantee measuring instruments by deriving the theory of health communication into a concept of verbal and nonverbal messages with interactive, encouraging learning, forming attitudes, and strengthening experiences indicators, while the intercoder reliability test is carried out using the Scott formula with a result of 1 for verbal messages because there is no difference in coding between coders, while the reliability level for nonverbal messages is 0.97 with there differences in coding between coders on the elements of action and expression.